Introducing a hermeneutics of cispicion: reading Sarah and Esau's gender (failures) beyond cisnormativity - Henderson-Merrygold, Jo (Library of Hebrew bible/Old Testament studies, 2026)
"Jo Henderson-Merrygold challenges cisnormative presuppositions that shape and, at times, occlude the variations in gender and sex exhibited by key characters in the ancestral narrative of Genesis 12-50. It charts the progression from Paul Ricoeur's hermeneutics of suspicion, through liberation, feminist and queer approaches. Focusing on Deryn Guest's queer and trans hermeneutics, Henderson-Merrygold then offers a new strategy for reading against fixed, binary gender assumptions, where a character's sex always matches that assigned at birth"--